Information complexity of weakly singular integral equations - Makhkamov, K. Sh.; Pereverzev, S. V. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We establish the exact power order of information complexity for integral equations whose kernels have power singularities and free terms belong to the corresponding Hölder space.